Subregion-Specific Modulation of Excitatory Input and Dopaminergic Output in the Striatum by Tonically Activated Glycine and GABAA Receptors - Adermark, Louise; Clarke, Rhona B.; Ericson, Mia; Söderpalm, Bo (Frontiers in Systems Neuroscience, 2011)
The flow of cortical information through the basal ganglia is a complex spatiotemporal pattern of increased and decreased firing. The striatum is the biggest input nucleus to the basal ganglia and the aim of this study was to assess the role of inhibitory GABAA and glycine receptors in regulating synaptic activity in the dorsolateral (DLS) and ventral striatum (nucleus accumbens, nAc). Local field potential recordings from coronal brain slices of juvenile and adult Wistar rats showed that GABAA receptors and strychnine-sensitive glycine receptors are tonically activated and inhibit excitatory input to the DLS and to the nAc. Strychnine-induced disinhibition of glutamatergic transmission was insensitive to the muscarinic receptor inhibitor scopolamine (10 µM), inhibited by the nicotinic acetylcholine receptor antagonist mecamylamine (10 µM) and blocked by GABAA receptor inhibitors, suggesting that tonically activated glycine receptors depress excitatory input to the striatum through modulation of cholinergic and GABAergic neurotransmission. As an end-product example of striatal GABAergic output in vivo we measured dopamine release in the DLS and nAc by microdialysis in the awake and freely moving rat. Reversed dialysis of bicuculline (50 μM in perfusate) only increased extrasynaptic dopamine levels in the nAc, while strychnine administered locally (200 μM in perfusate) decreased dopamine output by 60% in both the DLS and nAc. Our data suggest that GABAA and glycine receptors are tonically activated and modulate striatal transmission in a partially sub-region specific manner.